FRI0666 Increased prevalence of subclinical atherosclerosis in moderate-severe plaque psoriatic patients. (15th June 2017) - Vegas-Revenga, N; Martín-Varillas, J; Armesto, S; Drake, M; Portilla, V; Fuentevilla, P; Rueda-Gotor, J; Atienza, B; Domínguez-Casas, L; Fernández-Díaz, C; Blanco, R; González-Gay, M; et al.
Abstract : Background: Recent studies suggest that plaque psoriasis may be a risk factor for major adverse cardiac events. This has important therapeutic implications for cardiovascular (CV) risk stratification and prevention in patients with severe psoriasis. For that reason surrogate markers of subclinical atherosclerosis and CV mortality such as carotid plaques (CP) have been studied by carotid US examination. In most studies of psoriasis done before, the results have shown an increased prevalence of carotid plaques, but it is not always the rule. Objectives: To compare the prevalence of CP between patients with moderate-severe psoriasis and the general population. Methods: A cross-sectional study that included 40 patients with moderate- severe psoriasis (PASI>10, BAS>10%), that fulfilled definitions for initiating treatment with a biological agent and 40 age-, sex- and traditional CV risk factors- matched healthy control subjects. Patients with history of CV events, diabetes mellitus, and chronic kidney disease or body max index (BMI)>35 were excluded. Carotid ultrasonography was performed by a MyLab 70 scanner (Esaote; Genoa, Italy), then carotid plaque was defined according to the Manheim Consensus Conference criteria. Statistical analysis: Qualitative data were expressed as number and percentages and quantitative data as mean (SD). Student's t test or Mann-Whitney U were used to compare continuous variables, as appropriate. Chi2 test or Fisher test were used for qualitative variables. Results: The main data of the patients are summarized in the Table. It is important to highlight that it is based on a young population (mean age<40 years). The two groups did not present significant differences except for high sensitivity C-reactive protein (hsCRP) As expected given the age of the group, CV risk measured by SCORE was low (0%) with a mean of 0.2 us 0.15. No patient had a high-very high CV risk as measured by SCORE (≥5%). Patients with psoriasis had a long-standing disease (17.05±11.63 years). The presence of carotid plaques was found in a total of 10 patients with plaque psoriasis (25%), 5 of them had bilateral plaques) and one in the control group (2.5%) without bilateral plaques), p<0.003. Conclusions: Moderate-severe psoriasis is associated with increased prevalence of carotid plaques. Disclosure of Interest: None declared